A literature and medicine special study module run by academics in general practice: two evaluations and the lessons learnt. Issue 2 (6th December 2004) - Jacobson, L; Grant, A; Hood, K; Lewis, W; Robling, M; Prout, H; Cunningham, A M
Abstract : This paper describes the design, delivery and evaluation of a nine week special study module on literature and medicine for third year undergraduate medical students, by tutors from an academic department of general practice. Three weeks of taught seminars are followed by three weeks of one on one meetings between individual students and tutors, leading to a seminar led by, and based on, materials prepared by the student. The final three weeks of the course are dedicated to completion of essays about areas chosen by students for in depth study. The course was evaluated on two separate occasions, using two different techniques: the first evaluation used a focus group technique to identify and explore relevant themes; the second used nominal group theory to assess whether the course worked educationally, and how it could be improved. In the main, the course was judged to meets its aims, with generally positive student comments, albeit with caveats and reservations. The subject matter was intellectually challenging for students and tutors. Further research into the optimal size for such groups, and a more formal evaluation of tutors' experiences is required.